1985
DOI: 10.1902/jop.1985.56.12.752
|View full text |Cite
|
Sign up to set email alerts
|

Cell and Fiber Attachment to Demineralized Dentin from Normal Root Surfaces

Abstract: The study assessed connective tissue and epithelial responses to dentin specimens (obtained from normal roots of human teeth) after surface demineralization. Rectangular dental specimens with opposite faces of root and pulpal dentin were prepared from beneath root surfaces covered by periodontal ligament. One-half of the specimens were treated with citric acid, pH 1, for 3 minutes, while the remainder served as untreated control specimens. Specimens were implanted vertically into incisional wounds on the dorsa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 8 publications
2
49
0
Order By: Relevance
“…The objective of acid conditioning is to remove the smear layer (after mechanical root preparation) as well as sufficient inorganic matrix, exposing the collagen fibers without excessive destruction of the ultrastructural characteristics which would otherwise delay remineralization (Garrett et al, 1978;Polson et al, 1983). This altered root surface may provide a substrate that promotes chemotaxis, migration, and attachment of periodontal cells encouraging connective attachment to the denuded root surface (Fernyhough and Page, 1983;Hanes and Polson, 1989;Hanes et al, 1985;Polson and Hanes, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…The objective of acid conditioning is to remove the smear layer (after mechanical root preparation) as well as sufficient inorganic matrix, exposing the collagen fibers without excessive destruction of the ultrastructural characteristics which would otherwise delay remineralization (Garrett et al, 1978;Polson et al, 1983). This altered root surface may provide a substrate that promotes chemotaxis, migration, and attachment of periodontal cells encouraging connective attachment to the denuded root surface (Fernyhough and Page, 1983;Hanes and Polson, 1989;Hanes et al, 1985;Polson and Hanes, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…The protein layer formation is followed by the adherence of platelets and deposition of fibrin forming a network into which cells can migrate and get trapped. It has also been found that on a root surface without well exposed collagen fibers, the fibrin network only opposes but cannot get attached (Polson and Proye[4], Hanes, Polson and Ladenheim[5]. On the other hand, a well-demineralized root surface with exposed collagen fibrils is considered highly thrombogenic.…”
Section: Discussionmentioning
confidence: 99%
“…Hence root biomodification procedures have been introduced by using a variety of agents to detoxify, decontaminate and demineralize the root surface, thereby removing the smear layer and exposing the collagenous matrix of dentin and cementum [19]. Since then various root conditioners have been used which include e.g., citric acid, tetracycline HCI, EDTA, phosphoric acid, and hydrogen peroxide, enamel matrix proteins, recombinant human growth factors, platelet-rich plasma, and dentin bonding conditioner.…”
Section: Mechanical Methodsmentioning
confidence: 99%